Evil plans : having fun on the road to world domination - MacLeod, Hugh, 1965- (Portfolio/Penguin, 2011)
A new collection of irreverent wisdom and cartoons celebrates offbeat examples of how to enjoy work and life by engaging in happiness-promoting activities that are likely to incite the wrath of others.